The solutrean site of Olival do Arneiro (Rio Maior) - Cardoso, João Luís (2020)
The Solutrean site of Arneiro, or Olival do Arneiro, was identified by Manuel Heleno in 1942 and successively explored by him, in several intermittent campaigns of limited duration, until October 1944. It had already been the subject of a preliminary study in the seventies by Zbyszewski and collaborators. However, the authors were not aware of the contents of Manuel Heleno’s field notebooks with importante informations on the spatial distribution of materials, as a result of the ditches that were opened, as well as their typology and stratigraphy. Such elements appear essential for the framing of the results now presented, corresponding to the study of the whole collection, in the light of new morphometric and morphological criteria performed. In this way, the study of the 30 bifacial points identified and separated from the rest of the collection by O. da Veiga Ferreira, constituting to date the most important set of solutrean points from one single place of the Portuguese territory, was completed by the study of the remaining part of the original set, consisting of 391 bifacial points in different stages of execution belonging to the Museu Nacional de Arqueologia collections, of which only 51 are near the final stage of execution. The general conclusion obtained through the different analytical methodologies adopted led to the integration of this second set of pieces also in the Solutrean techno-complex. However, as there is no possibility of confronting this operative chain with another one known to be solutrean or more modern, it remains to demonstrate its true chronology.